KOORDINASI CAMAT DALAM PEMBANGUNAN DAERAH PESISIR DI KECAMATAN GAUNG KABUPATEN INDRAGIRI HILIR TAHUN 2016 - Merwanto, Yogi Gusfar; Anwar, Khairul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Sub-district Coordination in the development of coastal areas in Gaung Subdistrict, Indragiri Hilir Regency in 2016 is coordinating sub-district strategic plans into regional development planning and implementation programs related to issues and characteristics as well as potential coastal areas. Based on the Report on the Implementation of Regional Government (LPPD) of the Gaung Subdistrict of Indragiri Hilir Regency in 2016, in general the physical realization of the development budget has been going well, but has not touched the main objective of the environmentally sound development plan or has not been harmonized and the synergy between the Annual Work Program (RKT) 2016 with a Strategic Plan (Renstra) for coastal area development related to issues and the potential of the Gaung sub-district as a coastal area. The formulation of the research problem is how the coordination of sub-district heads in the development of coastal areas in the District of Gaung, Indragiri Hilir Regency in 2016, and the factors that influence the coordination of sub-districts in the development of coastal areas in 2016. The aim of the study was to determine the coordination of sub-district heads in the development of coastal areas in the District of Gaung, Indragiri Hilir Regency in 2016 and the factors that influenced the coordination of sub-districts in the development of coastal areas in 2016. The research method used is descriptive qualitative method with data collection instruments including interviews, observation and documentation studies related to the research objectives. The results of the study illustrate that the subdistrict head in coordinating the subordinate work units and sub-district level work units in planning and implementing development tends to be oriented towards improving general programs in realizing community welfare, but ignoring or not optimally directing and harmonizing insightful development environment related to the characteristics of coastal areas, such as the lack of preservation / prevention of natural damage, and the development or empowerment of fishermen or copra farmers in coastal areas in Gaung District in 2016. Keywords: Coordination, Development, Coastal Areas.